Design and Implementation of a Virtual Reality (VR) Urban Highway Driving Simulator for Exposure Therapy: An Interdisciplinary Project and Pilot Study - Francisca Melis; Ricardo Sánchez; Luz María González; Pablo Pellegrini; Jorge Fuentes; Rodrigo Nieto (Psychiatry International)
Exposure therapy approaches are recognized as effective treatments for specific phobias; however, certain phobias, such as fear of driving on urban highways, present unique challenges in order to expose the patient to the triggering stimuli in a safe, accessible, and controlled manner. In this context, we developed a virtual reality (VR) computerized driving simulator based on a local urban highway, and an accompanying clinical protocol to provide exposure therapy for patients with observed fear of driving on urban highways. We recruited eleven patients for this pilot study, where safety and tolerability as well as clinical and functional improvement were explored. We found that the driving simulator was safe and well tolerated by patients, with a notable 82% of patients successfully completing in vivo exposure, and there being a consistent trend in reduced anxiety scores using standardized testing. Nine patients successfully engaged in live exposures in a real freeway after participating in this VR-based exposure therapy protocol. The creation of an immersive and realistic VR environment based on a local urban highway for treating this phobia proved feasible and well-tolerated by participants. The intervention’s ability to engage patients who might otherwise have avoided traditional exposure therapies is noteworthy. Future research should aim to replicate this study with a larger and more diverse sample to enhance the generalizability of the findings.